PENINGKATAN HASIL BELAJAR IPA PADA POKOK PEMBAHASAN TENTANG SIFAT-SIFAT CAHAYA DENGAN METODE EKSPERIMEN PADA SISWA KELAS VA DI SDN 024 SAMARINDA UTARA TAHUN PEMBELAJARAN 2016/2017 - Ratna Khairunisa (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This research is based on the students' lack of understanding about the properties of light. This research uses classroom action research (PTK), the research procedure used is, planning, action, observation, and reflection. This research is conducted II The cycle each cycle consists of two meetings. The problems in cycle I are followed up in the next cycleThe purpose of this study was to improve the learning outcomes of science by using experimental method, VA class students in SDN 024 North Samarinda. Subject of this research is student of class of SD SDN 024 North Samarinda while object of this research is Experiment Method. The results of data analysis in this study proves that the results of learning properties of light by using the Experimental Method has increased from the average pre cycle value of 60 with percentage of 40.4% of students who complete then experience an increase in Cycle I ie the average value to 70 , 3 with the percentage of learning mastery 54,7% and Cycle II increased again with the average value 89,7 with 100% completeness study percentage. The conclusion of this research is that the improvement of learning result of the properties of light using Experimental Method has a good improvement from cycle I and cycle II with very good category.Keywords: Experimental Method and Science Study Results